EFEKTIVITAS PENERAPAN STANDAR OPERASIONAL PROSEDUR KANAL DONASI DOMPET DHUAFA JAWA TENGAH SEBAGAI MEDIA CROWDFUNDING DALAM MENDUKUNG PERTUMBUHAN ZAKAT INFAK DAN SEDEKAH - Muhammad Asrul Khaya; Chandra Warsito (Kampus Akademik Publiser, 2024)
Abstract. The effectiveness of the SOP can be seen from the achievement of indicators that have been successfully applied consistently, realizing the vision and mission, being the main reference for performance, and being a tool for coordination and communication between fields and protection when something bad happens to the institution. By knowing the effectiveness of the SOP of the Dompet Dhuafa Central Java donation channel, we can see the increase in crowdfunding carried out by the donation channel to realize the maximum collection of zakat, infaq and sadaqah funds. This research uses a qualitative approach with a case study design. Data collection was carried out using interview techniques with all Dompet Dhuafa Central Java Donation Channel managers, observation, and documentation. Data analysis techniques include data collection, data reduction, data presentation, data verification and conclusion drawing. The results showed that the application of SOP as a crowdfunding media until now still does not have a target in fact the donation channel only aims to make it easier for people to make donations and is in accordance with donation operational standards. In addition, there is transparency in the amount of donations that have been collected. The application of the SOP is still not maximized in the collection of zakat, infaq and sadaqah funds. Therefore, the SOP on the donation channel of the dhuafa wallet can be concluded to be ineffective. But it is able to assist in collection through easy and transparent information technology.